Entorno inmersivo para el entrenamiento de operación de estación de bombeo de agua y sistema contra incendio. - Iza Toapanta, Carlos Daniel (2021)
This project has been developed with the aim of creating a 3D virtual reality simulator with immersion capacity for training in the automation area, becoming a training solution in the monitoring, control and operation of a water pumping station and fire system reducing the cost of implementation and risk. Models and plans were generated with a design software for the lifting of the industrial infrastructure of the virtual environment and the system to emulate, which with the use of the Unity3D graphic engine develops a greater detail of realism through the virtualization of the elements involved in the process. This graphic engine generates animations that allows the monitoring, regulation and automation of the water pumping station and fire fighting system from the virtual environment implemented with the aim of executing operational training processes, said system allows the operator to have an interaction with controls of processes in a realistic and interactive way. Furthermore, this graphic engine allows the integration of external devices with the platform, recreating sensations that the operator places at the remote site through its integrated sensors. The interface of peripheral devices such as the Oculus Rift virtual reality glasses was made, which allows interaction and immersion between the user and the virtual environment to complement the learning experience. Within the immersive environment, the operator can see the status of the process and the actions generated through the virtual objects and instruments created in the 3D environment.